Microscopic Calculations of Low-Energy Fission within the Constrained Molecular Dynamics (CoMD) Model: Preliminary Results - Vonta, N.; Souliotis, G. A.; Fountas, P. N.; Bonasera, A.; Veselsky, M. (HNPS Advances in Nuclear Physics, 2019)
The investigation of the mechanism of nuclear fission is a topic of current experimental and theoretical interest. In this work, we initiated a systematic study of low and intermediate energy fission calculations using the Constrained Molecular Dynamics (CoMD) code. The code implements an effective interaction with a soft isoscalar part and with several forms of the density dependence of the nucleon symmetry potential. In addition, CoMD imposes a constraint in the phase space occupation for each nucleon restoring the Pauli principle at each time step of the evolution of the nuclear system. In this work, we present results for the reactions p (27 MeV) + 232Th and p (63 MeV) + 232Th and compare them with recent experimental data. It appears that the CoMD code is able to describe the complicated many-body dynamics of the fission process especially for the higher-energy fission reaction. Proper adjustment of the parameters of the effective interaction and further improvements of the code are necessary to achieve a satisfactory quantitative description of low-energy fission where shell effects play a definitive role.